Introduction to Journal of South American Earth Sciences special issue on “Magmatism of southernmost South America” - Navarrete, César (2021)
Fil: Navarrete, César. Laboratorio Patagónico de Petro-Tectónica. Universidad Nacional de la Patagonia San Juan Bosco. CONICET, Consejo Nacional de Investigaciones Científicas y Técnicas. Argentina.